(untitled) (Mustansiria Dental Journal, 2019)
Twenty fully edentulous subjects ranging from 50-80 years old .The subjects were selected from patients attending the prosthetic department in medical technical institute Baghdad in middle technical university . The aim of this study was to evaluate the influence of oats on the changes in composition (zn) (mg) in saliva of edentulous patients after wearing of new complete dentures. The results suggest that (Oats) diet exerted significant influence in concentration mg in edentulous patient and significant difference in concentration of Zn in the treatment group who received new complete dentures.